Verkehrsträgerübergreifende Markttransparenz bei der SNCF. Katalysator für den Wettbewerb im Personenfernverkehr. - Blome, Christian; Sauter-Servaes, Thomas (DVV Media Group, 2008)
Preise und Gesamtreisezeiten von Bahnfahrten können auf vielen Distanzen mit dem Luftverkehr konkurrieren, vermeintlich altmodische Produkte wie der Nachtzugverkehr interessante alternative Zeitfenster bieten. Nur ist dies den Konsumenten nicht bewusst. Mehrere Studien zeigen, dass die Nutzung des Verkehrsträgers Bahn durch eine unrealistische Reisepreis- und Reisezeitwahrnehmung negativ beeinflusst wird.

Long haul rail passenger traffic can - with regard to fares and journey times - compete effectively with airline service offers on many routes. Habitual travellers by air are not aware of the attractive rail fares on offer since their internet tariff search tends to be limited to monomodal air transport information systems. Rail operators should, therefore, aim for increased market transparency that covers other means of transport as well. The enhanced awareness of other carriers' price offers should thus serve to destabilize travellers' habitual travel-related behaviour. Innovative inter- and multimodal mobility solutions are dependent on multi-faceted awareness and a resultant post-monomodal mobility culture. France's state-owned rail carrier SNCF is the pioneer of the 'EcoComparateur' internet service that facilitates the simultaneous search for fares on offer by road, rail and air transport operators. This French instrument of comparison is regarded as a successful entry into the age of simple and speedy multimodal travel information although certain refinements are needed in order to achieve a really fair price comparison and to enhance the competitiveness of the various sales and marketing tools at hand.
Transport operators' market transparency - an important aspect in regard to the competitiveness of long haul rail passenger transport service offers.
Keywords: Verkehr; Verkehrsnachfrage; Wettbewerb; Personenfernverkehr; Schienenpersonenverkehr; Luftverkehr; Kostenrechnung; Preisvergleich; Markttransparenz; Reisezeit; Wahrnehmung; Verkehrsmarkt; Verkehrsleistung; Verkehrsangebot; Verkehrsdienstleistung; Hochgeschwindigkeitsverkehr